Asymmetric intramolecular C-H insertion of N-tosyl diazoimine intermediate from triazole derivative by axially chiral dirhodium(II) carboxylate complex - Lu, Wenjie; Murai, Takuya; Kyan, Ryuji; Kobayashi, Yusuke; Kawabata, Takeo; Furuta, Takumi (Synlett)
The asymmetric intramolecular C-H insertion of an in situ generated diazoimine intermediate derived from N-tosyl-1,2,3-triazoles was investigated. Among the chiral paddlewheel dirhodium(II) complexes screened, only C 2 -symmetric-like dirhodium(II) carboxylate complexes bearing axially chiral amino acid derivatives as ligands proved to be effective in asymmetric induction.This catalyst afforded 2,3-disubstituted tetrahydrofurans with reasonable enantioselectivity for the cis-isomer.